2007
DOI: 10.1086/521032
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Genetic Assessment of 1,433 Sequence Variants of Unknown Clinical Significance in the BRCA1 and BRCA2 Breast Cancer–Predisposition Genes

Abstract: Mutation screening of the breast and ovarian cancer-predisposition genes BRCA1 and BRCA2 is becoming an increasingly important part of clinical practice. Classification of rare nontruncating sequence variants in these genes is problematic, because it is not known whether these subtle changes alter function sufficiently to predispose cells to cancer development. Using data from the Myriad Genetic Laboratories database of nearly 70,000 full-sequence tests, we assessed the clinical significance of 1,433 sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
537
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(548 citation statements)
references
References 37 publications
9
537
1
1
Order By: Relevance
“…BRCA1 c.5194-12G4A had been predicted to be deleterious using a multifactorial LR model. 15 Here we show that it induces, in the minigene assay, the complete loss of the normal transcript and its replacement by an out-of-frame mRNA form (Figure 1b). After submission of this work, Whiley et al 17 have reported the same major splicing defect observed in a lymphoblastoid cell line from a patient carrying this mutation.…”
Section: Evaluation Of Bioinformatics Predictions Of Splicing Alteratmentioning
confidence: 57%
See 2 more Smart Citations
“…BRCA1 c.5194-12G4A had been predicted to be deleterious using a multifactorial LR model. 15 Here we show that it induces, in the minigene assay, the complete loss of the normal transcript and its replacement by an out-of-frame mRNA form (Figure 1b). After submission of this work, Whiley et al 17 have reported the same major splicing defect observed in a lymphoblastoid cell line from a patient carrying this mutation.…”
Section: Evaluation Of Bioinformatics Predictions Of Splicing Alteratmentioning
confidence: 57%
“…15 It was reported with no effect on splicing, 18 but another study 19 reported an effect in patient RNA. These discrepancies may reflect differences in RNA quality or stability of the relevant transcripts.…”
Section: Evaluation Of Bioinformatics Predictions Of Splicing Alteratmentioning
confidence: 98%
See 1 more Smart Citation
“…BRCA1 and BRCA2 variants that were not considered pathogenic and/or were not recognized by the Breast Cancer Information Core (BIC) (http://research.nhgri.nih.gov/bic/) were not reported. 47 …”
Section: Multiplex Ligation-dependent Probe Amplification Screening Amentioning
confidence: 99%
“…For OR related to co-occurrence, we used the formula proposed by Easton et al 29 Co-occurrence was considered exclusively as the presence of a mutation in trans of the same gene, with the exception of cases with a recognizable biallelic phenotype. For families where the genetic test could be extended to at least one relative, OR of cosegregation of disease and variant were evaluated according to Thompson et al 30 For this analysis, we assumed the age-specific risks and penetrance estimated by Marroni et al 31 for the Italian population.…”
Section: In Silico Analysismentioning
confidence: 99%